6-Carbohydrazonamidepurines: Convenient Precursors for 4,8-Disubstituted Pyrimido[5,4-d]pyrimidines - Rocha, Ashly; Bacelar, Ana H.; Fernandes, Joana; Proenca, M. Fernanda; Carvalho, M. Alice (Synlett, 2014)
A series of 4-arylamino-8-(alkyl or aryl)hydrazidepyrimido[5,4-d]pyrimidines was obtained efficiently from 6-carbohydrazonamidepurines by reaction with piperidine. The 6-carbo-hydrazonamidepurines were generated selectively by the reaction of 6-imidatopurine with hydrazides under acidic conditions.
Keywords: rearrangement; ring opening; ring closure; substituent effects; fused-ring systems; heterocycles